2013
DOI: 10.1590/s1677-5538.ibju.2013.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factor for Korean patients with renal cell carcinoma and venous tumor thrombus extension: application of the new 2009 TNM staging system

Abstract: Purpose: To study the surgical outcomes of radical nephrectomy with thrombectomy and to determine prognostic factors for survival of Korean patients with renal cell carcinoma (RCC) and venous tumor thrombus. Materials and Methods: A total of 124 patients with RCC and venous tumor thrombus who underwent radical nephrectomy and thrombectomy were included in this retrospective study. Cancer-specific survival (CSS) and recurrence-free survival (RFS) rates were analyzed retrospectively according to various prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
1
17
1
3
Order By: Relevance
“…This can be explained by differences in the applied inclusion criteria and/or patients' characteristics (e.g. higher proportion of patients with metastatic disease in other studies) [3,5,6,11,12]. The presence of metastasis, lymph node-positive status and lymphovascular invasion, high Fuhrman grade and high ASA performance status were negative predictors for DSS.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This can be explained by differences in the applied inclusion criteria and/or patients' characteristics (e.g. higher proportion of patients with metastatic disease in other studies) [3,5,6,11,12]. The presence of metastasis, lymph node-positive status and lymphovascular invasion, high Fuhrman grade and high ASA performance status were negative predictors for DSS.…”
Section: Discussionmentioning
confidence: 88%
“…Bertini et al [15] showed reduced survival of patients with friable thrombus consistency compared with solid IVC thrombi. Also, a low body mass index (BMI) and the presence of symptoms at initial diagnosis are independent risk factors for survival as shown by Cho et al [12], whereas higher BMI was shown to be associated with better post-operative performance, at least for OS. Further, independent risk factors for survival were positive surgical margin and the presence of necrosis in the gross pathology specimen as Coons et al [16] could show in a study of 128 patients with a T3b disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Последний благодаря быстроте, легкости выполнения и возможности работы на всех органах брюшной полости позволяет успешно осуществлять тромбэктомию при тромбах, исходящих из опухоли как правой, так и левой почки. У 1 (3,8 Атриотомия была расширена вверх, кровь аспирирована аппаратом Cell-Saver, из предсердия и грудного отдела НПВ удален плотный тромб. Попытки удалить опухолевый тромб из печеночного отдела НПВ оказались безрезультатны из-за плотной фиксации к интиме последней.…”
Section: Introductionunclassified